IMPLEMENTATION OF FINGER PAINTING TECHNIQUE IN CHILDREN WITH SPECIAL NEEDS SLOW LEARNERS IN CULTURAL ARTS LEARNING IN GRADE III ELEMENTARY SCHOOL - Syahrul Amri; Riana Nurhayati (SOSIOEDUKASI, 2026)
Slow learners have below-average learning ability and commonly experience difficulties in fine motor skills and creativity, requiring learning approaches that are concrete, gradual, and multisensory. This study aims to describe the planning, implementation, and evaluation of the finger painting technique in improving the creativity and fine motor skills of a special-needs student categorized as a slow learner in Cultural Arts learning in Grade III of SDN 002 Sangkulirang. A descriptive qualitative approach was employed, with a slow-learner student (initials ADM) as the research subject, supported by the classroom teacher and the student's parent as informants. Data were collected through moderate participant observation, semi-structured interviews, and documentation, validated through source and technique triangulation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The results show that the planning was designed simply and adaptively using concrete media; implementation proceeded gradually across three sessions, from teacher modeling to instruction without examples and finally free creative expression; and evaluation emphasized the individual learning process. The implementation of finger painting was shown to improve confidence, hand-finger coordination, and creativity, indicating its potential as an alternative instructional strategy for Cultural Arts in inclusive elementary schools.